FRI0394 Neuropathic pain is associated with skin thickness in systemic sclerosis patients. (15th June 2017) - Sousa-Neves, J; Cerqueira, M; Santos-Faria, D; Silva, J Leite; Afonso, C; Teixeira, F
Abstract : Background: Systemic Sclerosis (SSc) is a connective tissue disorder characterized by fibrosis of skin and internal organs, vasculopathy and systemic inflammation. To date, few studies assessed pain in SSc patients, (1) namely the neuropathic component. Data is also scarce on defining possible neuropathic pain (NP) predictors in these patients. Objectives: To determine if patients with SSc have a higher prevalence of NP compared with a group of age and sex matched controls and study possible associations between NP and SSc clinical variables. Methods: The study evaluated patients diagnosed with SSc fulfilling the SSc classification criteria of the American College of Rheumatology (ACR), older than 18 years old and followed up at our Rheumatology Unit. Forty-eight patients with mean age of 56.98±12.73 years and mean disease duration of 9.77±6.12 years were included. Comparison group comprised 45 age and sex matched controls. Patients and controls were consecutively evaluated at our Unit and NP in 4 questions questionnaire (DN4) was used for assessing the presence of NP. In SSc patients, skin involvement was also evaluated clinically by the modified Rodnan skin thickness score (mRSS) ranging from 0 to 51. Hand mobility (HAMIS) and SSc Severity Scale (SScSS) were also calculated and relevant clinical variables of the disease were collected. Parametric and nonparametric tests were used for comparative analysis. Multivariate logistic regression was used to identify factors associated to NP. Statistical significance was defined as P<0.05. Results: In our study, prevalence of NP assessed by DN4 was significantly higher in SSc patients comparative to controls (56.2% versus 13.3%, p<0.001). In addition to age and sex, presence of diabetes (p=0.541) was also similar in both groups. In SSc group, patients with and without NP showed some statistically significant differences (table 1 ). Multivariate logistic regression revealed that only mean mRSS (odds ratio [OR] =1.90, 95% confidence interval [CI] 1.01 to 3.55, p=0.045) was independently associated with the presence of NP. Conclusions: To the best of our knowledge, this is the first study evaluating the prevalence of NP in SSc patients in comparison with age and sex matched controls. NP was significantly more prevalent in patients with SSc. Skin thickness assessed by mRSS was independently associated with the presence of NP. References: Schiei O et al. Prevalence, severity, and clinical correlates of pain in patients with systemic sclerosis. Arthritis Care Res (Hoboken). 2010 Mar; 62(3):409–17. Disclosure of Interest: None declared